A Comparative Study of the Retention Force of Flexible Clasps for Non-Metal Clasp Removable Partial Dentures in Different Undercuts (An In-Vitro Study) (Journal of Hama University, 2021)
The metallic appearance of removable partial denture clasps is not acceptable for most patients. Recently, non-metallic clasp removable partial dentures have appeared in which all elements of framework from metal except the clasp’s retention arm of flexible acryl which is part of the flexible acrylic base. This contributed to overcoming the undesirable metallic appearance of the removable partial dentures’ chromium-cobalt clasps.The aim of this research is to make a laboratory comparison of retention force between chromium-cobalt clasps at a retention depth of 0.25 mm and flexible clasps at three retention depths (0.25 -0.50 - 0.75 mm). The research sample consisted of 48 clasps, divided into four groups. Each group consists of 12 clasps. A metal mold of the first upper molar was made. And an acrylic base was made for this metal mold. The 48 clasps were made according to the type of material and the depth of retention for each group. The data were analyzed using the t-student test (P